Interdisciplinary applications of electronic collaboration approaches and technologies - Kock, Ned F., 1964- (Information Science Reference, 2013)
"This book addresses the design and implementation of e-collaboration technologies, assesses their behavioral impact on individuals and groups, and presents theoretical considerations on links between the use of e-collaboration technologies and behavioral patterns"--Provided by publisher.